Investigation of surface enhanced Raman spectroscopy for hemozoin detection in malaria diagnosis - Chen, Keren (2018)
We report two methods of surface enhanced Raman spectroscopy (SERS) for hemozoin detection in malaria infected human blood. In the first method, silver nanoparticles were synthesized separately and then mixed with lysed blood; while in the second method, silver nanoparticles were synthesized directly inside the parasites of Plasmodium falciparum.